The Empowerment of Girls in the Classroom - Noriany, Orli (Wydawnictwo Naukowe UAM, 2015)
The general topic of the research is the empowerment of girls in the classroom. The research focuses on the increase of the motivation of girls and their belief in their ability, the creation of warm and close communication between the girls and the teacher, and the changes in technology in the 21st century – all with the goal of empowering the achievements of girls in the field of mathematics and in essence minimizing the differences between girls and boys in the field. From our experience, girls do not empower themselves in the field of mathematics. Girls allow boys to dominate the lessons, to manage the class discussion, to contribute of their knowledge – and girls remain silent. When afterschool enrichment classes in mathematics are recommended to boys and girls, the number of boys exceeds the number of girls, and in actuality, beyond the recommendations, the girls do not attend these courses. Already in the elementary school, the girls lag behind, and this staying behind causes them to make their choices accordingly and thus they lose an important economic resource. We are certain that it is possible to make a change, and we will begin with our attitude toward the girls in the classroom. We will look at our behaviors as teachers, effective behaviors for the promotion of teaching and learning, and we will apply these behaviors to girls, implementing a corrective preferential reference in our behavior.
Wzmocnienie pozycji dziewcząt w klasie
Keywords: girl empowerment; girl motivation; belief in ability; communication; teacher effective behaviors